2008
DOI: 10.1111/j.1440-1681.2008.04902.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection and Kallikrein–kinin System in Acute Myocardial Ischaemia in Mice

Abstract: 1. Acute myocardial ischaemia and reperfusion trigger cardioprotective mechanisms that tend to limit myocardial injury. These cardioprotective mechanisms remain for a large part unknown, but can be potentiated by performing ischaemic preconditioning or by administering drugs such as angiotensin-I-converting enzyme (kininase II) inhibitors (ACEI). 2. This brief review summarizes the findings concerning the role of tissue kallikrein (TK), a major kinin-forming enzyme, kinins and kinin receptors in the cardioprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…The beneficial effects of angiotensin-converting enzyme inhibition in hypertension, cardiovascular and renal disease can be partially attributed to kinin accumulation resulting from the activation of the B2 receptor [16,17] . Previous animal studies suggested that kallikrein/kinin protects against myocardial apoptosis after ischemia/reperfusion injury [18,19] . In our study, delivery of the kallikrein gene protected against cardiomyocyte apoptosis in SHRs; therefore, this gene could potentially be used to treat hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of angiotensin-converting enzyme inhibition in hypertension, cardiovascular and renal disease can be partially attributed to kinin accumulation resulting from the activation of the B2 receptor [16,17] . Previous animal studies suggested that kallikrein/kinin protects against myocardial apoptosis after ischemia/reperfusion injury [18,19] . In our study, delivery of the kallikrein gene protected against cardiomyocyte apoptosis in SHRs; therefore, this gene could potentially be used to treat hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular pressure and rate were recorded from a fluid-filled balloon tied into the left ventricle (isovolumic heart). Increasing doses of OK (1,2,4,8,16,32,64,128,256, 512 ng) were injected as a bolus into a port of the perfusion apparatus close to the coronary ostia. Subsequent injections were made only after blood pressure returned to baseline.…”
Section: Measurement Of Ornitho-kinin-induced Coronary Vasodilationmentioning
confidence: 99%
“…A number of observations have focused on Lys-BK as a potential mediator of endogenous cardiovascular protective mechanisms. This is due to the fact that KKS components are localized in the heart and in the vascular tissues (1)(2)(3)(4). Lys-BK is released during ischemia, causing beneficial cardiac effects and contributing to the cardioprotective effects of preconditioning (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation of kininase expression and activity has been reported in several vascular pathologies [36][37][38][39]. Consequently, inhibition of ACE enhances kinin stability and promotes vascular sprouting in animal models as well as in human cardiovascular patients, partly via the B 2 R and partly via other mechanisms [13,9,[40][41][42]. Using angiotensin II receptor type 1 knockout mice, Li et al demonstrated the involvement of both kinin receptors and NO signaling in ACE inhibitor-mediated angiogenesis in hindlimb ischemia [9].…”
Section: Nicolle Kränkel Phdmentioning
confidence: 99%